2015
DOI: 10.1071/he14098
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in primary school adherence to the NSW Healthy School Canteen Strategy in 2007 and 2010

Abstract: Proportion of schools adhering to strategy guidelines had increased slightly, however, most continue to list red items for regular sale. SO WHAT? For health policies to improve public health they need implementation. Findings suggest more work is required, particularly in small schools, rural schools and non-government schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 16 publications
(9 reference statements)
5
33
1
Order By: Relevance
“…Similar to this study, literature spanning 10 years has shown that ‘unhealthy’ foods are more commonly purchased from public school canteens; there is inconsistent buy‐in from public school parents; and the role of public school canteens is to provide healthy food, promote healthy eating and support the school healthy eating curriculum . In addition, public school canteen compliance with guidelines, regardless of State/Territory mandates, was found to be moderate to low . While the schools included in this study have voluntarily incorporated healthy options within their school canteen, a comparison of these findings to the Australian public school canteen literature suggest that school canteen guidelines may not be achieving the desired effects.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar to this study, literature spanning 10 years has shown that ‘unhealthy’ foods are more commonly purchased from public school canteens; there is inconsistent buy‐in from public school parents; and the role of public school canteens is to provide healthy food, promote healthy eating and support the school healthy eating curriculum . In addition, public school canteen compliance with guidelines, regardless of State/Territory mandates, was found to be moderate to low . While the schools included in this study have voluntarily incorporated healthy options within their school canteen, a comparison of these findings to the Australian public school canteen literature suggest that school canteen guidelines may not be achieving the desired effects.…”
Section: Discussionsupporting
confidence: 66%
“…1,3,22 In addition, public school canteen compliance with guidelines, regardless of State/Territory mandates, was found to be moderate to low. 6,7,23,24 While the schools included in this study have voluntarily incorporated healthy options within their school canteen, a comparison of these findings to the Australian public school canteen literature suggest that school canteen guidelines may not be achieving the desired effects.…”
Section: Discussionmentioning
confidence: 93%
“…This reduced the relative size of the intervention effect at 24‐month compared to that reported at 12‐month follow‐up. Such changes were surprising given evidence suggesting the policy implementation had been largely stable prior to study commencement . Implementation improvements within control schools may indicate potential contamination after the initial intervention ceased through sharing of resources, or learnings by intervention with control group schools.…”
Section: Discussionmentioning
confidence: 90%
“…Differences in the implementation of nutrition policies are also apparent by a number of school factors. In Australia for example, rural school canteens had significantly poorer implementation of a mandatory school canteen policy [17]. While such findings suggest that additional efforts to support policy implementation in rural schools may be required [17], providing such support across a population of schools that are geographically dispersed represents a considerable challenge to health policy makers and practitioners.…”
Section: Introductionmentioning
confidence: 99%